To solve the expression \(8 \times 10^4 - 2.7 \times 10^2\), we need to convert both terms to the same power of ten for easier subtraction.
First, we can express \(2.7 \times 10^2\) in terms of \(10^4\):
\[ 2.7 \times 10^2 = 2.7 \times 10^2 \times \frac{10^2}{10^2} = 2.7 \times 100 = 270 \]
So, we need to express it as \(0.027 \times 10^4\):
\[ 2.7 \times 10^2 = 0.027 \times 10^4 \]
Now, substitute this back into the original expression:
\[ 8 \times 10^4 - 0.027 \times 10^4 = (8 - 0.027) \times 10^4 \]
Calculating the subtraction:
\[ 8 - 0.027 = 7.973 \]
Thus, we have:
\[ (8 \times 10^4 - 2.7 \times 10^2) = 7.973 \times 10^4 \]
In standard form, the answer is:
\[ \boxed{7.973 \times 10^4} \]